Foreign Workers In Malaysia: An Assessment of Covid-19 Impact on Migrant Workers in Malaysia - Ahmad Zaharuddin Sani B. Ahmad Sabri; Roziya Abu (Proceeding International Conference on Information Technology and Business, 2020)
In a global public health and economic crisis such as the one we were facing, it was through the only humane affair to treat everyone with care and dignity, regardless of nationality and social class. Migrant workers deserved protection because of the simple virtue – they were human. The basic protection of human should be part of their human rights. Malaysia had been relying heavily on foreign workers in our economy. The data on foreigners represented around 14 to 16% of the total employed persons in the country since 2010. This figure included both documented and undocumented foreign workers by designing the household survey. This paper sought to elaborate the importance of protecting migrants’ workers in Malaysia. The paper discussed about an overview of this trends during Covid-19 cases in Malaysia. The current protection measures were introduced to migrant workers so that it was able to be proceeded into the reason why we had to care of the workers. This paper discussed the efforts taken by Malaysian government in responds to the spread of Covid-19 among migrants’ workers in Malaysia. Despite of the accusation of neglecting and harassing foreign workers in Malaysia during this pandemic, Malaysia was taking positive and humane action in taking care of our own sovereignty of our country.Keywords: Pandemic Covid-19, Migrant Workers, Malaysia Sovereignty, Human Rights, Pandemic Prevention Measurement